RANCANG BANGUN SISTEM INFORMASI KLINIK PRATAMA ROSSAMA DI KOTA PRABUMULIH BERBASIS WEB - Suhartini; iwan setiawan; Riza Prasetio (STEKOM PRESS, 2023)
Rossama Pratama Clinic is one of the health service providers for the community, which is located on Street Taman RT/RW 01/03 Sukajadi Village, East Prabumulih District, Prabumulih City, South Sumatra Province. The lack of information conveyed to the public has resulted in a lack of public knowledge about the Rossama Prabumulih Clinic Pratama Prabumulih because the information administration system carried out at this clinic is still manual, namely people who want to know about the latest information about the clinic must come directly so that it is more effective and efficient, because take a lot of time to arrive at the clinic. Therefore, the researcher will create a web informationsystem for the Rossama Pratama Clinic which will be accessed via a browser using the PHP programming language with the help of UML design to help design the system that will be created. The method of developing the system is using the Waterfall method. With this website, hopefully it will help people save time when they want to go to the clinic or seek treatment from home.